The 3rd International Conference on the Palaeontology of South-East Asia - Choong Chee Meng, Avalon Chin Soon Mun, Nurul Aishah Hanafi, Ask, . (2013)
Welcome to Universiti Teknologi PETRONAS and the Third International Conference on the Palaeontology of South East Asia. We have left neighbouring Thailand for this third meeting of the ICPSEA series to gather here in the small Malaysian community of Seri Iskandar. Most of you are spending evenings in Ipoh, our closest city, 40 km to the north.